Enhancing 21st Century Skills in the EFL Classroom: Exploring Teachers' Implementation of Group Activities and Assignments - Marwa Marwa; Nurfaisal Nurfaisal; Mualiardi Mualiardi; Raudhah Awal; Hengki Irawan (AL-ISHLAH: Jurnal Pendidikan, 2024)
This qualitative study was carried out to investigate how English teachers integrated 4C skills (communication, creativity, critical thinking, and collaboration) into EFL classroom. This study involved two English teachers from an English study program in one university in Pekanbaru, Riau as the research participants. The qualitative data was collected by using interview, observation, and documentation. The researchers analyzed the interview transcripts, observational fieldnotes, and screenshoot documents following the steps of qualitative data analysis by coding, grouping, synthesizing, and making themes and descriptions to answer the research questions. The study reveals that the English teachers integrated the 4C skills into students' learning group activities/assignments via making videos for English learning, making power point for class presentation, making class projects to produce learning products, and having asynchronous online classroom discussions via Google classroom platform. These four major class activities/assignments given by the English teachers were intentionally aimed at developing students’ communication skill, creativity, critical thinking, and collaboration. This study concludes that the four students’ typical learning group activities/assignments instructed by teachers can be used as templates to integrate and develop students’ 4C skills in ELT classes. Future research directions in developing 21st-century skills can be multifaceted, addressing various gaps and limitations in assessment methods, technology integration, cultural contexts, equity and access, and teacher training and professional development.